Instrument for Student Attitudes Assessment in Science Learning: A Review and Bibliometric Analysis - Dini Rosdiane Rusdiyanto; Bibin Rubini; Didit Ardianto (Gemilang Maju Publikasi Ilmiah (GMPI), 2023)
This research aimed to provide a bibliometric study on the keyword